Inducible IL-7 Hyperexpression Influences Lymphocyte Homeostasis and Function and Increases Allograft Rejection - Schreiber, Maria; Weigelt, Marc; Karasinsky, Anne; Anastassiadis, Konstantinos; Schallenberg, Sonja; Petzold, Cathleen; Bonifacio, Ezio; Kretschmer, Karsten; Hommel, Angela (Frontiers in Immunology, 2019)
The IL-7/IL-7R pathway is essential for lymphocyte development and disturbances in the pathway can lead to immune deficiency or T cell mediated destruction. Here, the effect of transient hyperexpression of IL-7 was investigated on immune regulation and allograft rejection under immunosuppression. An experimental in vivo immunosuppressive mouse model of IL-7 hyperexpression was developed using transgenic mice (C57BL/6 background) carrying a tetracycline inducible IL-7 expression cassette, which allowed the temporally controlled induction of IL-7 hyperexpression by Dexamethasone and Doxycycline treatment. Upon induction of IL-7, the B220+c-kit+ Pro/Pre-B I compartment in the bone marrow increased as compared to control mice in a serum IL-7 concentration-correlated manner. IL-7 hyperexpression also preferentially increased the population size of memory CD8+ T cells in secondary lymphoid organs, and reduced the proportion of CD4+Foxp3+ T regulatory cells. Of relevance to disease, conventional CD4+ T cells from an IL-7-rich milieu escaped T regulatory cell-mediated suppression in vitro and in a model of autoimmune diabetes in vivo. These findings were validated using an IL-7/anti-IL7 complex treatment mouse model to create an IL-7 rich environment. To study the effect of IL-7 on islet graft survival in a mismatched allograft model, BALB/c mice were rendered diabetic by streptozotocin und transplanted with IL-7-inducible or control islets from C57BL/6 mice. As expected, Dexamethasone and Doxycycline treatment prolonged graft median survival as compared to the untreated control group in this transplantation mouse model. However, upon induction of local IL-7 hyperexpression in the transplanted islets, graft survival time was decreased and this was accompanied by an increased CD4+ and CD8+ T cell infiltration in the islets. Altogether, the findings show that transient elevations of IL-7 can impair immune regulation and lead to graft loss also under immune suppression.